Sex-specific associations of autism spectrum disorder with residential air pollution exposure in a large Southern California pregnancy cohort. (November 2019) - Jo, Heejoo; Eckel, Sandrah P.; Wang, Xinhui; Chen, Jiu-Chiuan; Cockburn, Myles; Martinez, Mayra P.; Chow, Ting; Molshatzki, Noa; Lurmann, Frederick W.; Funk, William E.; Xiang, Anny H.; McConnell, Rob
Abstract: Autism spectrum disorder (ASD) affects more boys than girls. Recent animal studies found that early life exposure to ambient particles caused autism-like behaviors only in males. However, there has been little study of sex-specificity of effects on ASD in humans. We evaluated ASD risk associated with prenatal and first year of life exposures to particulate matter less than 2.5 μm in aerodynamic diameter (PM2.5 ) by child sex. This retrospective cohort study included 246, 420 singleton children born in Kaiser Permanente Southern California (KPSC) hospitals between 1999 and 2009. The cohort was followed from birth through age five to identify 2471 ASD cases from the electronic medical record. Ambient PM2.5 and other regional air pollution measurements (PM less than 10 μm, ozone, nitrogen dioxide) from regulatory air monitoring stations were interpolated to estimate exposure during each trimester and first year of life at each geocoded birth address. Hazard ratios (HRs) were estimated using Cox regression models to adjust for birth year, KPSC medical center service areas, and relevant maternal and child characteristics. Adjusted HRs per 6.5 μg/m 3 PM2.5 were elevated during entire pregnancy [1.17 (95% confidence interval (CI), 1.04–1.33)]; first trimester [1.10 (95% CI, 1.02–1.19)]; third trimester [1.08 (1.00–1.18)]; and first year of life [1.21 (95% CI, 1.05–1.40)]. Only the first trimester association remained robust to adjustment for other exposure windows, and was specific to boys only (HR = 1.18; 95% CI, 1.08–1.27); there was no association in girls (HR = 0.90; 95% CI, 0.76–1.07; interaction p-value 0.03). There were no statistically significant associations with other pollutants. PM2.5 -associated ASD risk was stronger in boys, consistent with findings from recent animal studies. Further studies are needed to better understand these sexually dimorphic neurodevelopmental associations. Graphical abstract: Image 1 Highlights: First trimester pregnancy exposure to PM2.5 was robustly associated with increased risk of ASD only in boys. The male-specific results were consistent with findings from recent animal studies. There were no statistically significant associations between other ambient pollutants and ASD. The approach in a large population may be useful for studying interactions of air pollution with other ASD risk factors. Abstract : First trimester pregnancy exposure to fine particles was robustly associated with subsequent increased risk of autism spectrum disorder that was specific to boys.